Small antenna design for tv white space application - Tan, Hong Yong (2018)
This thesis presents the design of a wide band micro-strip antenna for wireless communication for operation at 340 MHz to 600 MHz (receiving and transmitting respectively). In this master dissertation, a one port network will be examined and the design requirements for the antenna include the S11 parameters which also known as the return loss to be less than or equal to 10 dB for a 50Ω reference impedance. The design of the wide band should be planar, simple structure, low in cost and the fabricating process should not be complex. The advantage of the design of the antenna is that no lumped element is required to be soldered on, for example, the surface mount components, hence the reduction in the production cost. The study includes the construction of a three-dimensional antenna model, antenna simulation and the analysis of results based on the various outputs results of the CST Microwave Studio Finite Difference Time Domain (FDTD) software package.